Application of esterase polymorphism to specify population genetic structure of Engraulis encrasicolus (Pisces: Engraulidae) in the Black and Azov Seas - (:unkn) unknown (My University, 2013)
Genetic structure of anchovy populations was studied using genetic-biochemical markers. Anchovy samples collected between 1980 and 2006 from different Black Sea regions (off the Bulgarian, Turkish, Ukraine, and Georgian coasts) as well as from the Sea of Azov were analyzed. Three methods of electrophoresis were applied: starch gel electrophoresis, vertical polyacrylamide electrophoresis, and isoelectric focusing on thin polyacrylamide ampholine gel plates. On the base of long-term monitoring of allelic frequencies of the polymorphic non-specified esterases loci (EST-1* and EST-2*), wintering migration of Azov anchovy may have alternative routs along the western Black Sea coasts. Typical Azov anchovy winter together with the Black Sea anchovy form the mixed populations along the Ukrainian, Georgian, and Turkish Black Sea coasts. Azov anchovy was also registered along Bulgarian coast during the second part of May and July. The results allow supposing the north-western Black Sea as complementary spawning areas of Azov anchovy.
Применение полиморфизма эстераз в исследованиях популяционно-генетической структуры Engraulis encrasicolus (Pisces: Engraulidae) в Чёрном и Азовском морях
Генетическую структуру популяций хамсы (E. encrasicolus) анализировали с применением генетико-биохимических маркеров. Было проанализировано 1692 образца хамсы из различных районов Чёрного моря – у берегов Болгарии, Турции, Украины и Грузии и 399 образца из Азовского моря, собранных с 1980 по 2006 гг. Три метода электрофореза были использованы в этом исследовании: электрофорез в крахмальном геле, вертикальный полиакриламидный электрофорез, изоэлектрическое фокусирование на пластинах с полиакриламид амфолиновом геле. На основе долгосрочного мониторинга частот аллелей полиморфных локусов (EST-1* and EST-2*) неспецифических эстераз показано, что зимовальная миграция азовской хамсы может осуществляться вдоль западного побережья Чёрного моря. Генетические данные показали, что у берегов Синопа (Турция) наряду с черноморской зимовала и азовская хамса. Смешанные популяции этих рыб во время зимовки были обнаружены как у берегов Украины, так и Грузии. Азовская хамса, наряду с черноморской, обнаружена у берегов Болгарии также во второй половине мая и июне. Генетические маркеры позволяют предположить, что размножение азовской хамсы может осуществляться в северо-западной части моря.
Keywords: азовская и черноморская хамса; генетические маркеры; электрофорез; изоэлектрическое фокусирование (ИЭФ); миграционные пути